Empowerment of nurses: A key to stroke patients' satisfactions - Shayan Alijanpour; Zahra Aslani; Nasrollah Alimohammadi; Fariba Taleghani (Wolters Kluwer Medknow Publications, 2020)
Background: Stroke is a major cause of disability around the world. Different studies have shown the inadequate knowledge and skills of nurses to educate and manage stroke patients. Therefore, stroke patients are facing many challenges in their lifetime. In this study, we investigated the effects of nursing empowerment on stroke patients' satisfaction. Materials and Methods: This cross-sectional study is the fifth stage (evaluation phase) of action research study that was conducted on 29 stroke patients from Alzahra hospital, Isfahan, Iran, during 2013-2014. Workshops, pamphlets, and booklets were used for nursing empowerment. The stroke patients have been trained by empowered nurses. The data gathering tool that was the researcher-made survey questionnaire included the characteristics of patients, participants' satisfaction with self-care training and nurses' performances. T-test was used for the analysis of the obtained data. Results: Twenty-seven (93.10%) cases mentioned that "they would try to follow all the received trainings". Twenty-three (73.10%) cases were satisfied with self-care training. Majority of patients, 25 (85%) participants were satisfied with the training performances by the empowered nurses and 24 (82.80%) cases were highly satisfied with the nurses' training method. Conclusions: Most patients were satisfied with the self-care training held by the nurses. Based on the obtained data by questionnaires, the nurses' performance and their training methods were directly associated with a high satisfaction level in stroke patients. Therefore, improving the skills and knowledge of nurses could be a potential approach for increasing the satisfaction levels among stroke patients.